Evidence of validity of the Brazilian version of the Cancer Behavior Inventory - Brief Version - Cláudia Jeane Lopes Pimenta; Thaíse Alves Bezerra; Cleane Rosa Ribeiro da Silva; Kaisy Martins de Albuquerque Madruga; Tatiana Ferreira da Costa; Rômulo Lustosa Pimenteira de Melo; Kátia Neyla de Freitas Macedo Costa (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To analyze the validity evidence of the Brazilian version of the Cancer Behavior Inventory - Brief Version. Method: Methodological study, conducted between November and December 2021, with 140 patients undergoing hospital cancer treatment in João Pessoa, Paraíba, Brazil. Psychometric analyses were performed in the adapted version, using exploratory factor analysis and correlation with correlated constructs. Results: A two-factor and 10-item model was evidenced. The cumulative variance explained about 61% the shared variance of the items. Satisfactory values were observed for the factors in the analyses of composite reliability (0.89 and 0.91, respectively), internal consistency (0.86 and 0.91, respectively) and ORION (0.89 and 0.85, respectively). The expected correlations of self-efficacy with quality of life (convergent) and with anxiety and depression (divergent) were evident. Conclusion: The Brazilian version of the instrument showed evidence of validity, being considered reliable to assess the self-efficacy of patients undergoing cancer treatment.